RUSSIAN LEGISLATION IN THE FIELD OF STATE-CONFESSIONAL RELATIONS IN THE CONTEXT OF CONTEMPORARY CONFESSIONAL LEGAL POLICY - E. A. Avdeyev (Гуманитарные и юридические исследования)
The subject of this study is the contemporary condition of legal policy in the field of state-confessional relations in the Russian Federation. The purpose of this article is a theoretical analysis of the contemporary condition of legislation in the field of state-confessional relations and evaluation of prospects of its further development. Revival of religion, increase in the number of religious organizations in the Russian society are objective factors that actualize the necessity to determine the correct vector of legal policy in confessional area, to improve legislation in the sphere of regulation of state-confessional relations, and to provide conditions for a legal dialogue between government and confessional institutions.